2019
DOI: 10.1016/j.ppees.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits modulate plant community responses to alien plant invasion

Abstract: It is well known that alien plant invasion modifies the composition and diversity of resident plant communities, yet our ability to predict patterns of vegetation responses to invasion is hampered by a poor understanding of which functional traits make some resident plants more or less vulnerable to invader impacts. For example, resident species may be more likely to persist and coexist with the invader if they display different strategies of resource use (i.e. high niche differences) or if they share similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…This is further supported by a positive shift of the community trait space along the plant height axis under invasion of I. glandulifera (Garnier and Navas ). Moreover, these results are in line with the recent study of Fried et al (), that showed that invasion by the highly competitive alien plant Humulus japonicus resulted in a shift of the native community towards competition related trait values for SLA, plant height and growth form. Although observed trait patterns might also be caused by differences in abiotic (soil) conditions, considering that we used a space‐for‐time substitution to compare invaded and uninvaded communities, we expect this to be unlikely.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is further supported by a positive shift of the community trait space along the plant height axis under invasion of I. glandulifera (Garnier and Navas ). Moreover, these results are in line with the recent study of Fried et al (), that showed that invasion by the highly competitive alien plant Humulus japonicus resulted in a shift of the native community towards competition related trait values for SLA, plant height and growth form. Although observed trait patterns might also be caused by differences in abiotic (soil) conditions, considering that we used a space‐for‐time substitution to compare invaded and uninvaded communities, we expect this to be unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…This peripheral location of both invader hypervolumes in the trait space suggests the importance of trait distinctiveness for invasion success following the empty niche hypothesis (Elton , Moles et al , MacDougall et al ). Trait differentiation between invader and community was more pronounced for the leaf economics traits, and seemingly absent for plant height, potentially suggesting that niche differences are more important than fitness differences in driving the patterns (MacDougall et al , Drenovsky et al , Fried et al ). However, we cannot fully exclude that fitness differences are also partly involved, since 1) trait differentiation was also found for the leaf area axis and 2) leaf economics traits can also relate to fitness differences (Leishman et al , van Kleunen et al , Kunstler et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Thomsen et al (2016) made a convincing case for increased use of this method in order to better differentiate the ways that invaders alter community structure (i.e., the diversity of the resident community vs. that of the resultant community). Studies that have taken this approach have been able to characterize both plant community response to invasion and the positioning of an invader in the functional structure of invaded communities (Thomsen et al 2016, Loiola et al 2018, Parra‐Tabla et al 2018, Sodhi et al 2019, Fried et al 2019). Generally, the results of these studies vary, showing how resident plant communities can either experience an increase in functional diversity as a result of invasion (Hejda and de Bello 2013, Loiola et al 2018) or a decrease (Thomsen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the results of these studies vary, showing how resident plant communities can either experience an increase in functional diversity as a result of invasion (Hejda and de Bello 2013, Loiola et al 2018) or a decrease (Thomsen et al 2016). Yet, the approach consistently sheds light on how invasive plants tend to act as a biotic filter, disassembling native communities (Parra‐Tabla et al 2018, Fried et al 2019, Sodhi et al 2019). However, synthetic interpretation is confounded by the lack of differentiation between naturalized and invasive alien species in some of these studies (Loiola et al 2018, Parra‐Tabla et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to biotic resistance, native communities should repel less competitive invaders (for instance through reduced survival rates) or invaders sharing similar functional features; however, it has been reported that IAS overcome biotic resistance by competition-induced trait shifts [79]. In addition, fine-scale experimental studies [79,80] indicated that functionally distinct plant species might have a better chance to succeed in the invasion process being better competitors or avoiding direct competition and co-occurrence with closely related natives, occupying different spatio-temporal niches [17,81]. Perhaps, a great sharing of functional niches between the two subcommunities may hamper community invasibility (e.g., through competition), thus newly introduced species will likely become naturalized rather than invasive [77].…”
Section: Discussionmentioning
confidence: 99%